The Ethics of Learning. (19th May 2018) - Jagger, Paul
Abstract: Any practitioner of education, in all its forms, has a responsibility to behave in a professional manner. Indeed, who would not claim that they act professionally and are, therefore, a professional? With that in mind, Paul Jagger FBCS considers what those responsibilities might be and what ethical standards practitioners should follow.